Monogenic interferonopathies: Phenotypic and genotypic findings of CANDLE syndrome and its overlap with C1q deficient SLE. (8th November 2017) - Al‐Mayouf, Sulaiman M.; AlSaleem, Alhanouf; AlMutairi, Nora; AlSonbul, Abdullah; Alzaid, Tariq; Alazami, Anas M.; Al‐Mousa, Hamoud
Abstract: Objective: To report the clinical and genetic features of the first cases of chronic atypical neutrophilic dermatosis with lipodystrophy and elevated temperature (CANDLE) syndrome in an Arab population and to compare them with patients of C1q deficient systemic lupus erythematosus (SLE). Materials and Methods: This is a retrospective case series of patients with CANDLE syndrome and C1q deficient SLE seen at a single tertiary hospital. Medical records were reviewed for demographic data, clinical and laboratory features, histopathology and imaging findings, and response to therapeutic intervention. Descriptive data were summarized. Results: Three patients from unrelated families fulfilled the clinical manifestations of CANDLE syndrome. The disease onset was within the first 4 months of age. Two patients had uncommon features including uveitis, pulmonary involvement, aseptic meningitis and global delay. Skin biopsy showed heterogeneous findings. Genomic DNA screening was homozygous for mutation in PSMB8, (NM_004159.4:c.212C>T, p.T71M) in one patient and inconclusive for the other two patients. The comparison group was three patients with familial C1q deficient SLE from three unrelated families, who were born to consanguineous parents with at least one affected sibling. They presented with extensive mucocutaneous lesions, discoid rash and scarring alopecia. They required frequent admissions due to infections. Conclusion: This is the first report of CANDLE syndrome in an Arab population; our patients had heterogeneous phenotypic and genetic features with overlap manifestations with C1q deficient SLE. Both are monogenic interferonopathies. However, C1q deficient SLE had more systemic inflammatory disease.